Divergent Territories: Educational Planning Tools in The Face of Territorial Inequalities - Sebastião, João; Gonçalves, E. (16th European Sociological Association Conference 2024, 2024)
The current political and social debate on the need to reorganize the Portuguese state has resulted in the transfer of powers and services from the central state to the municipalities in various areas, including education. This is a structural change, since the education system has always been highly centralized and independent of regional or local communities. From 2022 onwards, the Intermunicipal Communities and Town Halls will develop their own education policies, tailored to their territories. Among the strategic planning mechanisms, the Regional Strategic Educational Plans and the Municipal Educational Charters are central. The collaboration of a team of sociologists in drawing them up in two highly unequal territories made it possible to analyze the territorial, social and cultural dynamics and reflect on their educational development strategies. A metropolitan municipality and a group of municipalities located in a rural area in the south of Portugal were analyzed. The first, heavily gentrified, has a highly qualified population with high purchasing power, where cultural diversity is seen as an advantage for the digitally-centered municipal economy. The other, rural, marked by demographic regression and ageing, with a poorly qualified population and reduced purchasing power, in which the growing presence of immigrants is disregarded by local institutions. The results point to strategies oriented towards a qualified and diversified educational offer in relation to the social and productive territory of the Metropolitan Area; and towards a “damage control” strategy in which education is considered an instrument for the survival of the rural hinterland.